Hydroplan 1988 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Hydroplan 1988 The 4th International Exhibition on Agricultural, Village and Urban Waterworks will be held from May 17-20, 1988 in Marseille